The Economics of Politics: Patronage and Political Selection in Italy - Federico Quaresima; Fabio Fiorillo (Center for Economic Studies and ifo Institute (CESifo), 2016)
This article investigates the patronage phenomenon in the italian, so called, Second Republic. In particular, the analysis argues that (ex) members of parliament are appointed to managerial boards in italian (partially) state-owned enterprises responding to political selection rationales. Indeed, direct political connections could be conceptualize as an instrument to control and reward politicians' loyalty throughout a legislature. Especially in a majoritarian electoral system, where the interests of political parties and districts may diverge, the formers would need patronage resource to assure themselves members of parliament loyalty when casting ballots. The results of the empirical investigation suggests that parliamentarians' loyalty does play a role in patronage appointments as well as the electoral result in the next electoral competition.
Keywords: D72; D73; 330; SOE; patronage; political selection; exit strategy